The effect of timber moisture content on epoxy bonded-in connection - Masbor, Muainnudin (2018)
Connections of timber structures using concealed bonded-in rods offer a solution to the efficient joining methods. However, the importance of certain basic joint characteristics, and the influence of moisture content are not yet fully understood. This paper describes a comprehensive experimental and numerical investigation into the fundamental material and joint geometry characteristics of rods bonded in to timber. The treatment type and level of moisture content both considered, along with test configuration that included rod and timber species. It was found that epoxy adhesives out-performed all other types investigated, and pull-out strengths can be significantly improved by indicating suitable moisture content and treatment. Moisture content at higher level sample exhibited higher pull-out strength. This indicates that the shear strength values of the tested specimens were affected by the moisture content and same result when tested with different type of treatment. There is a strong correlation between the moisture content of the wood, type of treatment and mean shear strength. Failure mode in moisture content and type of treatment is related to the anatomical properties of the wood that influences the wettability of adhesive used.